From physics to fish to folk: supporting coastal regional communities to understand their vulnerability to climate change in Australia. (30th December 2015) - Frusher, Stewart; van Putten, Ingrid; Haward, Marcus; Hobday, Alistair J.; Holbrook, Neil J.; Jennings, Sarah; Marshall, Nadine; Metcalf, Sarah; Pecl, Gretta T.; Tull, Malcolm
Abstract: Our oceans comprise valuable assets that provide a range of social and economic benefits directly and indirectly through provisioning, regulating, cultural and supporting services. Fisheries rely on these services and are regionally important industries for many coastal communities. With a growing population and increasing demand for seafood production, impacts from climate change that alter the productivity of marine ecosystems will have flow‐on implications for economic and social systems. As small coastal communities are often highly dependent on marine‐based activities they are also expected to experience greater impacts from changes in productivity of marine resources than their larger and/or non‐coastal counterparts. To assist coastal communities in evaluating their vulnerability to climate change we have developed a hybrid socio‐ecological vulnerability index that combines an ecocentric index – i.e., an ecological vulnerability index – with a sociocentric index that focuses on adaptive capacity as a measure of vulnerability, and embeds a sustainable livelihoods approach. Through the use of an on‐line tool, coastal communities can improve their understanding of their vulnerability to more appropriately adapt, embrace opportunities and minimize negative impacts that may arise from climate change and its effect on marine resource availability.